Critical Legal Studies as a Teaching Method, Against the Background of the Intellectual Politics of Modern Legal Education in the United States - Robert W Gordon (Legal Education Review)
I see the role of this paper as providing some perspective and background to Gerald Frug’s much more thorough and detailed account of some teaching methods of critical legal studies (CLS).